Characterization and quantitation of polyphenolic compounds in Senna splendida from the Northeast of Brazil - Maia, Irvila Ricarte de O.; Breuer, Andrea; Owen, Robert (Natural product communications, 2018)
A total of 27 polyphenolic compounds were detected, identified and quantitated in methanol extracts of various botanical parts of Senna splendida (Vogel) H.S. Irwin & Barneby. On a dry weight basis, the higher concentration of polyphenolic compounds was detected in the leaves (28.524 g/kg) and roots (13.884 g/kg). By contrast, the values in the flowers (6.331g/kg) and bark of Senna splendida (2.736 g/kg) were considerably lower. The major component in Senna splendida leaves was quercetin diglucoside, (7.887 g/kg), in the roots methoxy oxyresveratrol (4.485 g/kg), in the flowers quercetin-3-O-rhamnoside-4′-O-glucoside (2.885 g/kg), and in the bark quercitrin (quercetin rhamnoside; 0.881 g/kg). The composition of the polyphenolic compounds in the flowers, leaves and bark were dominated by flavonoids at > 98%, whereas the composition was quite different in the roots, of which the major components were napththapyrones (54 %) and stilbenes (39 %) with a very low contribution from flavonoids (5 %) and phenolic acids (2 %).
Gesehen am 16.09.2019